Perkembangan Media Edukasi Hadis dari Tradisi Lisan ke Era Digital - Aliyah Husna Ritonga; Rahmi Syahriza; Tonang Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the evolution of hadith educational media from the classical era to the digital age. By employing a qualitative method with a content analysis approach, this research aims to: (1) define the concept of hadith educational media, (2) describe its forms in the classical period, (3) explain its development in the modern era, and (4) analyze the challenges and opportunities of digital hadith media. The findings reveal that classical media such as oral transmission (sama’), manual writing on scrolls (shahifah), and the use of the pulpit (mimbar) relied on direct teaching, memorization, and physical artifacts to preserve and transmit hadith. In the modern period, media have expanded to include print, electronic, digital, interactive, and visual formats, enabling wider dissemination and more engaging learning experiences. However, the digital era brings challenges, including the spread of fabricated hadith (maudhu’), low digital literacy, commercialization of religious content, and a lack of scholarly oversight. Opportunities identified include broader access to authentic sources, innovative da’wah methods, youth involvement in digital preaching, digital preservation of manuscripts, and global academic collaboration. The study concludes that while digital transformation offers significant potential for Islamic education, it must be accompanied by scholarly verification, ethical guidance, and integration with classical learning traditions to ensure the integrity and authenticity of hadith transmission.